Georgias Transport and Logistics Strategy : Achievements to Date and Areas for Improvements - Benmaamar, Mustapha; Keou, Oceane; Saslavsky, Daniel (World Bank, Washington, DC, 2015)
This policy note describes the state of transport and logistics in Georgia, carries out a needs assessment and identifies the main areas for improvements.The purpose of this policy note is to develop a common understanding between the Government of Georgia (GoG) and its partners of the institutional and physical challenges which face the transport and logistics sector, and of a strategy for meeting these challenges in the medium-term. The policy note identifies the key strategic directions and actions which will enable the sector to grow and improve. It intends to help the Bank and the development partners to engage with the GoG in dialogue on the critical bottlenecks and to provide the Government with advice based on the Bank’s international experience. The strategic directions outlined in this policy note require institutional reforms. This is inevitably a long term process but one which will gradually improve Georgia’s Logistics Performance Index ranking and its trade and competiveness.